2016
DOI: 10.5601/jelem.2015.20.4.932
|View full text |Cite
|
Sign up to set email alerts
|

Mineral content of tree sap from the Subcarpathian region

Abstract: Tree sap has been used for centuries not only as a source of nutrients available in early spring but also as medicinal substance in folk medicine. Traditionally, it was used to treat various conditions, mostly anaemia and chronic fatigue. This study has been designed to establish the content of metallic elements (sodium, potassium, calcium, magnesium, zinc and copper) in sap collected from eight different species (silver birch, downy birch, hornbeam, Norway maple, boxelder maple, black walnut, black alder and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Very high mineral content in birch tree sap has been demonstrated, including copper, zinc, manganese and magnesium. although it is variable, depending on the individuals (Bilek et al, 2015b;Bilek et al, 2016b). At the same time negligible content of harmful substances in the birch sap has been found, eg.…”
Section: Introductionmentioning
confidence: 99%
“…Very high mineral content in birch tree sap has been demonstrated, including copper, zinc, manganese and magnesium. although it is variable, depending on the individuals (Bilek et al, 2015b;Bilek et al, 2016b). At the same time negligible content of harmful substances in the birch sap has been found, eg.…”
Section: Introductionmentioning
confidence: 99%
“…Correlation between 21studied mushroom species with regard to the content of detectable elements (heatmap) in mean values with presentation of a hierarchical tree plot significantly higher content of Cr and lower amount of Cd in the mushrooms studied by Doğan et al (2006) (Onder and Dursun 2006). Furthermore, in the case of T. versicolor, differences in a higher/lower content in the fruit bodies of this mushroom may be explained by its growth on Carpinus betulus L. or poplar trees (Kaszala et al 2003;Bilek et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In light of these studies, birch sap from central Europe can be considered primarily as a rich source of minerals, mainly copper, zinc and manganese. These minerals have a comprehensive impact on, among others, the human immune and reproductive systems and on the condition of skin, hair and nails [23,24,29,30]. At the same time, it was found that birch sap has fundamental restrictions, undermining its use as a potential raw material for the food industry.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, it was found that birch sap has fundamental restrictions, undermining its use as a potential raw material for the food industry. It is very susceptible to anthropopressure, which is particularly visible in the content of industrial and agricultural contaminants in birch sap: heavy metals, inorganic anions, residues of plant protection products and polycyclic aromatic hydrocarbons [30,31]. However, collecting birch sap from the forest environment, the least polluted ecosystem, solves these problems [32][33][34].…”
Section: Introductionmentioning
confidence: 99%